PENDEKATAN KONSELING PASTORAL TERHADAP REKONSILIASIKELUARGA DALAM KONTEKS PERUMPAMAAN ANAK YANG HILANG - Politon, Gloria; Sarananung, Millitia (LIMMUD: Jurnal Ilmu Keagamaan dan Sosial Humaniora, 2025)
ABSTRACT The family is the primary foundation in shaping individual character and spirituality. Within the dynamics of family life, conflicts and broken relationships often occur, necessitating a recovery approach that is not only psychological but also spiritual. This article aims to examine the pastoral counseling approach in the family reconciliation process, based on a theological reflection of the Parable of the Prodigal Son in Luke 15:11–32. Using a qualitative research method through literature study, this article analyzes the principles of forgiveness, grace, and relational restoration as core components of pastoral counseling. The results show that pastoral counseling provides a meaningful path toward healing family relationships through empathetic spiritual guidance grounded in Christian faith values. The Parable of the Prodigal Son offers a profound biblical narrative that portrays the dynamics of family reconciliation—from the parent-child relationship to sibling conflicts. This approach emphasizes the importance of repentance, unconditional acceptance, and open dialogue in building emotionally and spiritually healthy families. Keywords: pastoral counseling, family reconciliation, parable of the prodigal son, love, forgiveness.